2009
DOI: 10.1227/01.neu.0000346272.76537.dc
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Attenuates Microglial Cells and Astrocyte Activation and Decreases Interleukin-1b Level After Traumatic Brain Injury

Abstract: Objective-Our previous studies demonstrated that simvastatin promotes neurological functional recovery after traumatic brain injury (TBI) in rat; however, the underlying mechanisms remain poorly understood. The purpose of this study was to investigate the anti-inflammatory effect of simvastatin by measuring the level of cytokines and activation of glial cells.Methods-Controlled cortical impact injury was performed in adult male Wistar rats. The rats were randomly divided into three groups: sham, saline control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
86
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 36 publications
7
86
0
Order By: Relevance
“…TBI in rodents also increases levels of activated glial cells and proinflammatory cytokines, [34][35][36][37][38] and administration of these cytokines increases anxiety-like behaviors. [29][30][31][32] The aim of the present study was therefore to determine whether neuroinflammation is associated with the long-term maintenance of post-traumatic anxiety in an animal model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TBI in rodents also increases levels of activated glial cells and proinflammatory cytokines, [34][35][36][37][38] and administration of these cytokines increases anxiety-like behaviors. [29][30][31][32] The aim of the present study was therefore to determine whether neuroinflammation is associated with the long-term maintenance of post-traumatic anxiety in an animal model.…”
mentioning
confidence: 99%
“…Peri-injury and immediate postinjury immunosuppression have been found to be neuroprotective after TBI in rodents, resulting in increased structural preservation and improved functional outcomes. 104 Early administration of the immunosuppressant drugs, minocycline, statins, cyclosporin A, and FK506, have been shown to exert anti-inflammatory effects through suppression of micro-and astroglial production of IL-1b, TNF-a, and IL-6, resulting in reduced functional deficits, cerebral edema, and brain lesion volumes, [35][36][37][38]66 improving mitochondrial preservation, reducing dendritic spine loss, and improving cognitive performance and functional motor recovery. 105,106 Our previous investigation found that peri-injury Ibudilast treatment attenuated glial cell activation at the time of injury, resulting in reduced anxiety-like behaviors and immunological impairments after LFPI.…”
mentioning
confidence: 99%
“…Their actions favor a switch toward antiinfl ammatory phenotypes that may contribute to neuronal healing rather than damage ( Fig 2 ), a process observed in studies of animal models and cultured mouse microglial cells. Li et al 35 reported that mice treated with simvastatin had signifi cantly…”
mentioning
confidence: 99%
“…Glial activation is normally neuroprotective (26,32); however, the chronic inflammatory responses and exaggerated proinflammatory cytokine levels observed following injury initiate neurotoxic processes resulting in secondary tissue damage (20,(33)(34)(35), neuronal death (29,(36)(37)(38), secondary injury cascades (39)(40)(41)(42)(43) and neuronal hyperexcitability (28, 34, 38, 44). There is substantial support for chronic inflammation following TBI.…”
Section: Post-traumatic Anxiety Is a Leading And Devastating Consequementioning
confidence: 99%
“…Several studies have reported increased anxiety-like behavior in rodent TBI models, [29][30][31][32] including increased conditioned 33 and unconditioned 34 fear responses to both learned and novel stimuli. TBI in rodents also increases levels of activated glial cells and proinflammatory cytokines, [34][35][36][37][38] and administration of these cytokines increases anxiety-like behaviors. [29][30][31][32] The aim of the present study was therefore to determine whether neuroinflammation is associated with the long-term maintenance of post-traumatic anxiety in an animal model.…”
Section: -4mentioning
confidence: 99%